A multifunctional tripodal fluorescent probe for the recognition of Cr3+, Al3+, Zn2+ and F− with controllable ESIPT processes. (March 2019) - Zhang, Hong; Sun, Tao; Ruan, Qin; Zhao, Jiang-Lin; Mu, Lan; Zeng, Xi; Jin, Zongwen; Su, Shaobo; Luo, Qingying; Yan, Yiyong; Redshaw, Carl
Abstract: Three 4-(benzo[ d ]thiazol-2-yl)-2, 5-dihydroxybenzaldehyde fluorophores were introduced to construct a tripodal multifunctional ESPIT fluorescence probeL . The fluorescent analysis revealed that probeL exhibited excellent recognition capabilities towards Cr 3+, Al 3+, Zn 2+ and F − ions with large Stokes shifts. Furthermore, under optimal conditions, the detection limit of probeL towards Cr 3+, Al 3+, Zn 2+ and F − were low, of the order of 10 −8 M, which indicated that probeL was sensitive to these four ions. Interestingly, the fluorescent and 1 H NMR titration experiments revealed that the recognition mechanism of probeL towards the ions Cr 3+, Al 3+, Zn 2+ and F − were different. The presence of Cr 3+ and Al 3+ recovered the ESIPT, but the presence of Zn 2+ trigger a moderate deprotonation of the phenolic OH and induced an ESIPT red-shifted (60 nm) emission wavelength. Finally, the presence of F − completely deprotonated the free phenolic OH and a remarkable red-shifted (130 nm) ESIPT emission was observed. In other words, the ESIPT process of probeL is controllable. Furthermore, the utility of probeL as a biosensor in living cells (PC3 cells) towards Cr 3+, Al 3+ and Zn 2+ ions has been demonstrated. Graphical abstract: The ESIPT process of probeL is respectively controlled by the presence of Cr 3+, Al 3+, Zn 2+ and F − ions. Highlights: ProbeL exhibited excellent recognition capability towards Cr 3+, Al 3+, Zn 2+ and F − ions with large Stokes's shift. The detection limits of probeL towards Cr 3+, Al 3+, Zn 2+ and F − were very low, of the order of 10 −8 M. The ESIPT process of probeL is manipulative.